Association of different blood parameters with the early patency of Infarct related artery in ST elevation Myocardial Infarction, a comparative analysis - Manandhar, Reeju; Sun, Chaofeng (Nepalese Heart Journal, 2015)
Background and Aims: ST-segment elevation myocardial infarction(STEMI), a severe form of coronary heart disease signifies total occlusion of a coronary artery leading to myocardial necrosis, however about 10-20% of patient’s presents with a patent infarct-related artery on the initial angiogram. The availability of reliable markers for prediction of patency in infarct-related artery is very limited. Methods: We conducted a single centered retrospective study of STEMI patients undergoing primary percutaneous coronary intervention, to determine how various factors such as blood parameters differ in patients with patent infarct related artery to patients with total occlusion at the time of initial angiography done within 24hours of onset of symptoms and how they affect in outcome of the disease. Results: Mean Platelets Volume level (11.96 fL vs. 10.92 fL, p < 0.001), Lp (a) level (179.57 nmol/l vs 141.16 nmol/l, p < 0.001), CK-MB (290.2 vs. 190.98, p < 0.001), total cholesterol level (4.11 mmol/L vs. 3.8 mmol/L, p < 0.02) in total occlusion group were higher than in the patent infarct related artery group. Wall motion abnormality was 77.2% for 203 patients with total occlusion group and 54.2% for 83 patients with patent infarct related artery group (p<0.01). Mean hospital stay days were higher in total occlusion group as compared to the patent infarct related artery group (p < 0.01). Conclusions: Mean Platelet Volume, Lipoprotien(a), Total cholesterol, and CK-MB levels may play role in predicting patency of Infarct related artery in STEMI. Nepalese Heart Journal 2015;12(2):73-77